Precise intercombination transition rates in C+ and N2+ ions measured at a heavy-ion storage ring - Träbert, Elmar; Gwinner, G.; Knystautas, E. J.; Tordoir, X.; Wolf, Andreas (Journal of physics. B, Atomic, molecular and optical physics, 1999)
The slow electric dipole intercombination decay of the 2s2p2 4PJ levels in the B-like ions C+ and N2+ has been optically observed from ions circulating in a storage ring. The lifetime results are (7.95±0.07,104.1±0.5,22.05±0.07) ms for the J = ½,(3/2) and (5/2) levels in C+, and (1.32±0.05,13.9±0.2,3.30±0.07) ms for the same levels in N2+, respectively. This represents an improvement in precision by a factor of up to 10 compared to previous experimental results. The observed lifetime pattern is consistent with a number of theoretical predictions, removing discrepancies between experiment and theory that had been claimed previously.
Im Titel ist "2" hochgestellt
Gesehen am 01.12.2020